Labor politics in Latin America : democracy and worker organization in the neoliberal era - Posner, Paul W.; Mayer, Jean-François; Patroni, Viviana, 1957- (University of Florida Press, 2018)
Labor Politics in Latin America assesses the capacity of working class organizations to represent and advance working people's demands in an era in which capital has reasserted its power on a global scale. The book's premise is that the longer-term sustainability of development strategies for the region is largely connected to the capacity of working class organizations to secure a fairer distribution of the gains from growth.